2016
DOI: 10.4103/0976-237x.194101
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cross-sectional study on the prevalence of hypodontia in a target population of Al-Jouf Province, Saudi Arabia

Abstract: Aim:The purpose of this retrospective study was to determine the prevalence of hypodontia and to ascertain the need of interdisciplinary treatment for ensuing esthetic and functional problems in a target population of Al-Jouf Province, Saudi Arabia.Subjects and Methods:Using a dental administration software tool, a total of 1267 patients who presented to the outpatient clinics of the Orthodontic and Prosthodontic Departments between March 2015 and January 2016 were identified. Of those, 694 were females and 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
9
0
6
Order By: Relevance
“…(6) En este estudio, la frecuencia de hipodoncia fue muy similar a la indicada anteriormente. Asia y Europa presentan prevalencias diversas: un estudio en España en el 2017 reportó 0,9% (4), en Turquía en el 2016 se obtuvo un 6,2% (8) y en Arabia Saudita en el 2016 se registró un 6,1% (6).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…(6) En este estudio, la frecuencia de hipodoncia fue muy similar a la indicada anteriormente. Asia y Europa presentan prevalencias diversas: un estudio en España en el 2017 reportó 0,9% (4), en Turquía en el 2016 se obtuvo un 6,2% (8) y en Arabia Saudita en el 2016 se registró un 6,1% (6).…”
Section: Discussionunclassified
“…Una fortaleza del estudio es que la población estudiada no presentó diferencias étnicas al estar constituida por niños costarricenses de padres de la misma nacionalidad, ya que como se mencionó anteriormente, sí se han reportado diferencias en la frecuencia de anomalías dentales según la etnia (4,6,8).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Sajjad A, et al showed that the prevalence of hypodontia was 6.1% in Al-jouf province, Saudi Arabia and this is in consistent with our study. 17 On the other hand, Salem G . studied congenitally missing teeth in Jazan, Saudi Arabia with prevalence resulted to be 2.2%.…”
Section: Discussion:-mentioning
confidence: 99%